PREVENTION OF LEFT VENTRICLE SYSTOLIC DYSFUNCTION IN PATIENTS WITH ACUTE CORONARY SYNDROME WITH ST SEGMENT ELEVATION AFTER CARDIAC REVASCULARIZATION - A. L. Alyavi; B. A. Alyavi; M. L. Kenzhaev; S. R. Kenzhaev (Столичная издательская компания, 2016)
Aim. To study effects of bioflavonoid quercetin (corvitin) on left ventricle (LV) systolic dysfunction in patients with acute coronary syndrome with ST segment elevation (ACS+ST) after cardiac revascularization. Material and methods. 60 patients with ACS+ST (44,2±1,3 y.o.) were examined. Patients were admitted to hospital within 6 hours after complaints beginning. Patients were randomized in two groups. 30 patients of group A had standard therapy and cardiac revascularization. 30 patients of group B received corvitin additionally to standard therapy before cardiac revascularization. Echocardiography initially and stress-echocardiography with dobutamine after status stabilization (at 8-10 days of disease) were performed. Results. Dobutamine test (with low and high doses) showed myocardial viability in patients of group B. Patients of group A had irreversible LV systolic dysfunction in 32 % of segments. Corvitin slowed down LV dilatation progression in patients with ACS+ST. It resulted in the end-diastolic and end-systolic indexes did not change within 10 days. The LV ejection fraction was more increased in patients of group B in comparison with patients of group A. Conclusion. The early corvitin prescribing has positive effects on LV systolic function and prevents post-reperfusion complications.